2016
DOI: 10.1080/09638199.2016.1151545
|View full text |Cite
|
Sign up to set email alerts
|

The Feldstein–Horioka puzzle in South Africa: A fractional cointegration approach

Abstract: The Feldstein-Horioka puzzle (FH), that is the strong correlation between saving and investment in a world where obstacles to capital mobility are limited, has been studied extensively since it was exposed in 1980. Even though the theoretical and empirical literature has examined many of its potential causes, the puzzle persists. This paper aims at shedding further light on the issue by investigating the relationship between saving and investment in South Africa since 1946 using fractional integration and coin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
1
1
0
Order By: Relevance
“…Their results using the FMOLS and DOLS panel cointegration estimations showed only a slightly higher degree of capital mobility in African countries due to economic integration. Similar to the studies of Adedeji and Thornton (2007) and Bangake and Eggoh (2012), Gil‐Alana et al (2016) found that the saving retention coefficient in South Africa decreased after financial deregulation process, which was considered as an observed structural break around 1980.…”
Section: Literature Surveysupporting
confidence: 64%
See 1 more Smart Citation
“…Their results using the FMOLS and DOLS panel cointegration estimations showed only a slightly higher degree of capital mobility in African countries due to economic integration. Similar to the studies of Adedeji and Thornton (2007) and Bangake and Eggoh (2012), Gil‐Alana et al (2016) found that the saving retention coefficient in South Africa decreased after financial deregulation process, which was considered as an observed structural break around 1980.…”
Section: Literature Surveysupporting
confidence: 64%
“…It is noteworthy to observe that some attempts in testing the Feldstein–Horioka hypothesis for African countries have been made in the last decade and a half. Some important empirical investigations in this regard are, the studies conducted by Cooray and Sinha (2007), De Wet and Van Eyden (2005), Murthy (2005), Adedeji and Thornton (2007), Cyrille (2010), Bangake and Eggoh (2011, 2012), Kumar, Sen, and Srivastava (2014), Barros and Gil‐Alana (2015), Gil‐Alana, Andre, Gupta, Chang, and Ranjbar (2016), Raheem (2017). Adedeji and Thornton (2007) employed FMOLS and DOLS estimators allowing for heterogeneity and cross‐sectional dependence effects.…”
Section: Literature Surveymentioning
confidence: 99%